Report of CGIAR Digital Transformation Accelerator Strategy dialogue - Ojanji, Wandera; Dhulipala, Ram (International Livestock Research Institute, 2025)
Executive summary On 10 April 2025, during CGIAR Science Week at the United Nations Office in Nairobi, CGIAR convened over 300 stakeholders for the Digital Transformation Accelerator (DTA) strategy dialogue. This high-level event marked a significant milestone in CGIAR’s journey to become a leader in inclusive, data-driven transformation of food, land, and water systems. The dialogue introduced the vision, strategy, and flagship initiatives of DTA, an ambitious new CGIAR accelerator focused on harnessing digital innovation, artificial intelligence (AI), and big data to address global challenges in agriculture and sustainability, particularly in the global South.